Complex of chemical-technological and sanitary-hygienic quality indicators of the new pastry products of special nutrition - Kotlyar, Eugene; Topchiy, Oksana; Pilipenko, Lyudmila; Pуlуpenko, Inna; Sevastіanova, Elena (My University, 2017)
The publication is devoted to studying the original recipes of meat pastries for special nutrition, enriched with biologically active components at the expanse of vitaminized blended vegetable oils (VBVO) and protein-fatty emulsions (PFE) on their base, were elaborated. There were elaborated four recipes of pastries of chicken and turkey with PFE, included in recipes in the amount 15…20 % and with vitaminized blended vegetable oils of two-component and three-component composition in the amount 10 %. Pastry samples, prepared according to SSTC 4432:2005 were used as a control.
Keywords: кафедра технології м’яса і м’ясних продуктів; pastry products; vitaminized blended vegetable oils; кондитерські вироби; вітамінно-змішані рослинні олії; кондитерские изделия; витаминные смешанные растительные масла